Immediate and postponed results of surgery of tuberculosis in patients with HIV infection - A E. Suzdalnitskiy; S. I. Petrov; V. P. Petukhov; O. N. Novitskaya; O. V. Zhukova (Туберкулез и болезни лёгких)
The objective: to evaluate immediate and postponed results of surgical treatment of tuberculosis (TB) in patients with TB/HIV co-infection.Subjects and methods. 106 patients underwent surgery: 64 patients suffering from pulmonary tuberculosis (81.2% had resections, and 18.8% – thoracoplasty), 36 patients – tuberculous spondylitis (vertebral body resection in combination with anterior spondylodesis), and 6 patients – cerebral TB (removal of tuberculous lesions under neuronavigation). Development of complications in the postoperative period and tuberculosis relapses in the long-term period was assessed.Results. No severe and suppurative complications were observed in the postoperative period in patients with HIV/pulmonary TB and HIV/cerebral TB. In patients with HIV/TB spondylitis, complications were registered in 4/36 (11.1%) cases: in 2/4 – postoperative wound suppuration and in 2/4 – ligature fistulas. No relapse of tuberculosis was reported after lung resection in 45 out of 45 patients availabe for follow-up, after thoracoplasty in 10 out of 12 patients, after surgery due to tuberculous spondylitis – in 25 out of 27 patients, and cerebral tuberculosis – in 5 out of 6.